Community engagement approaches for Indigenous health research: recommendations based on an integrative review - Cheryl Barnabe; Chu Yang Lin; Adalberto Loyola-Sanchez; Elaine Boyling (BMJ Open)
Objective Community engagement practices in Indigenous health research are promoted as a means of decolonising research, but there is no comprehensive synthesis of approaches in the literature. Our aim was to assemble and qualitatively synthesise a comprehensive list of actionable recommendations to enhance community engagement practices with Indigenous peoples in Canada, the USA, Australia and New Zealand.Design Integrative review of the literature in medical (Medline, Cumulative Index to Nursing and Allied Health Literature and Embase) and Google and WHO databases (search cut-off date 21 July 2020).Article selection Studies that contained details regarding Indigenous community engagement frameworks, principles or practices in the field of health were included, with exclusion of non-English publications. Two reviewers independently screened the articles in duplicate and reviewed full-text articles.Analysis Recommendations for community engagement approaches were extracted and thematically synthesised through content analysis.Results A total of 63 studies were included in the review, with 1345 individual recommendations extracted. These were synthesised into a list of 37 recommendations for community engagement approaches in Indigenous health research, categorised by stage of research. In addition, activities applicable to all phases of research were identified: partnership and trust building and active reflection.Conclusions We provide a comprehensive list of recommendations for Indigenous community engagement approaches in health research. A limitation of this review is that it may not address all aspects applicable to specific Indigenous community settings and contexts. We encourage anyone who does research with Indigenous communities to reflect on their practices, encouraging changes in research processes that are strengths based.